Does Music Matter? Evidence from IPA transcription training in factors affecting foreign language sound perception - Dundon, Jack (My University, 2014)
Students participated in a six week linguistics training course called Ear Training, that involved perceiving sounds of the IPA and transcribing them. This course was part of a larger second year University of Edinburgh course called LEL:2B (linguistics and English language). Their scores in this Ear Training exam were compared with results in various musical tests and other information gathered from a questionnaire. Correlational and regression analysis showed that overall musical ability, particularly pitch perception and musical training, was strongly related to Ear Training score. These results suggest that high quality sound identification can be taught to people with good pitch perception abilities, which may or may not stem from musical training. This provides implications for the teaching of foreign language sound perception: that musical input may benefit the language classroom, and that greater emphasis on phonetic training may be advantageous and worthwhile.
Evidence supporting the link between musical ability and foreign language perception ability.
Keywords: Music and Language